New cases of probable skeletal tuberculosis from the Neolithic period in Hungary : a morphological study - Spekker, Olga (Acta Biologica Szegediensis, 2012)
The aim of this study is to present new data on the occurrence of tuberculosis (TB) in the Neolithic period of Hungary. The authors present results of the paleopathological investigation of skeletal remains from the Tisza culture tell settlement of Vésztô-Mágor, one of the largest Neolithic tells of the Great Hungarian Plain. The remains of 30 individuals were examined using standard macromorphological methods of bioarchaeology. Before the paleopathological examination of the series, sex and age at death of individuals and state of preservation of the observable skeletal elements were also recorded. In spite of the poor state of preservation, the osteoarchaeological series of Vésztô-Mágor showed a wide range of paleopathological alterations: skeletal traces of degenerative articular changes, traumas, haematological and infectious diseases were observed. This presentation focuses on 4 probable tuberculous cases. Most of the detected alterations (rib lesions, superficial vertebral changes/hypervascularisation and endocranial alterations) can be considered as atypical or early-stage TB lesions. Although a positive correlation seems to exist between these alterations and TB, they are not always pathognomonic to tuberculosis. These results contribute to improving our knowledge on the occurrence of TB in prehistoric populations of Hungary.